Environmental and economic comparison of semi-rigid and flexible base asphalt pavement during construction period. (15th March 2022) - Zhang, Rui; Tang, Naipeng; Zhu, Hongzhou; Zeng, Juan; Bi, Yanqiu; Xi, Yuan
Abstract: Sustainable design of pavements is necessary for achieving carbon neutrality, which is the important goal for green pavements. In order to investigate the impacts of major design parameters on the environmental and economic performances of asphalt pavement, process life cycle assessment (LCA) and process life cycle cost (LCC) methods were used. And this paper mainly focuses on the effects of pavement type, resilient modulus of subgrade, thickness of adjustable layer, traffic level and the bidirectional annual average daily traffic volume of two-axis six-wheel and above vehicles (AADTT) on environmental and economic performances of asphalt pavement. Then energy consumption, greenhouse gas (GHG) emission, construction budget and environmental economy cost of heavy traffic and medium traffic asphalt pavement were quantitatively analyzed during construction period. The results indicate that the energy consumption, GHG emission, construction budget and environmental economy cost of each layer of semi-rigid and flexible base asphalt pavement are the largest in the materials preparation stage, followed by the transportation stage and the construction stage. The above environmental and economic indicators are mainly influenced by AADTT, adjustable layer thickness and pavement type of asphalt pavement during construction period, while the resilient modulus of subgrade has minor effect on environmental and economic indicators. Overall, the energy consumption and GHG emission of the flexible base asphalt pavement are lower than that of the semi-rigid base asphalt pavement, although flexible base asphalt pavement has higher construction budget and environmental economy cost.